INFORMAL COMPARISON STUDY OF FACTORS INFLUENCING ACADEMIC PERFORMANCE OF KCSE: A CASE OF IMENTI SOUTH AND IMENTI CENTRAL IN MERU COUNTY - Kimathi, Faith Kagwiria; Kibaara, Dr. Tarsilla M.; Muriungi, Dr. Pamela (IJRDO- Journal of Educational Research, 2017)
Education is the best legacy a nation can give to her citizens, especially the youth. This isbecause the development of any society depends much on the educational standards of thenation. The purpose of the study was to determine factors that lead to dismal performance inKCSE examinations in Imenti Central, as compared to Imenti South Sub County in MeruCounty. The study established that schools in Imenti South perform better than schools in ImentiCentral partly because schools in Imenti South have more teachers, staffrooms, libraries, labs,books for staff and students. It was also established that schools in Imenti South Sub Countyperform because of high rates of student absenteeism in Imenti Central due truancy andsuspension. Poor parental participation in academic work of their children and lack ofcommunication between parents and students in Imenti Central could explain the differencesbetween students’ the two sub-counties.